(untitled) (Scientia Agropecuaria, 2017)
The first contact between consumers and the food product is usually the packaging and it’s labelling. Therefore, it is the primary means to generate consumer’s expectations. The aim of the present work was to evaluate the influence of nutritional and health claims on acceptance of salami with reduced sodium content, aimed at finding guidance for the product reformulation. Sixty consumers evaluated four samples of salami. The overall acceptance was evaluated using a nine-point hedonic scale, and the attributes color, tenderness, characteristic flavor and salt content, were evaluated by 7 – point just-about-right (JAR) scale. For the expectation test, overall liking of salami with reduced sodium content was evaluated by consumers under three conditions: (1) blind test (B); (2) expectation generated by nutritional and health claims (E), and (3) consumers re-tasted the salami having the nutrition and health claims available (R). Student’s t-tests performed on data indicated no significant differences (p > 0.05) between the mean acceptance under the blind (B) and real (R) conditions, although expectation ratings (E) were significantly higher than (B) (p ≤ 0.05). However, linear regression of (R - B) x (E - B) ratings revealed a major assimilation effect of expectation, especially under negative disconfirmation (E > B). Contrast effect was also observed, but to a lesser extent. The results showed that saltiness attribute was not decisive in decreased acceptance according to the JAR scale, but it was relevant in the aftertaste generated by adding salt substitutes. Finally, nutritional and health claims had little effect on consumer acceptance.